Application of infrared vibrational spectroscopy, coupled with multivariate statistical analyses, to analyze the effects of using Diuron based herbicides on Carioca beans (Research, Society and Development, 2023)
Diuron is an herbicide from the urea chemical group and, even though it is considered toxic and persistent in the environment, it is among the best-selling commercial herbicides in Brazil. The objective of this study is to analyze the infrared spectra of plant leaves treated with a Diuron based herbicide and those of the herbicide itself. To this end, two plantings of Carioca beans were carried out, and in the first planting, the herbicide was applied to the soil in controlled quantities, and, in the second planting, the herbicide was sprayed on the bean leaves, using dosages equal to those of the first planting. In the first planting, 13 infrared spectra of the leaves were obtained using pellet preparation techniques and the Spectrum 2000 spectrophotometer, from PerkinElmer. In the second planting, 25 spectra were obtained, using UATR techniques and the Spectrum Spotlight 400 FTIR spectrophotometer, from PerkinElmer. Using the spectra obtained from the second planting, it was demonstrated that washing the pulverized leaves with water was effective for removing the Diuron herbicide. The band at 1385 cm-1 proved to be sensitive to the amount of herbicide applied to the soil, as its intensity, only in the first planting, showed a significant change with the varying amount of herbicide applied. Therefore, it can be suggested that the band at 1385 cm-1 may be related to the presence of the herbicide or to the structural change of the plant.